La base de données. Figement - Grezka, Aude (Neophilologica, 2011)
At present fixity plays an important role in linguistic research because of its determining role in recognition systems. In this article we present ongoing research on fixity, in particular on creation of a database whose objective is to list all the frozen expressions, basing on formal criteria. Taking adverbial phrases as an example, we shall specify the criteria allowing us to point to absolute fixity before tackling the question of its relative aspect.